PAF-Receptor in inflammatory versus non inflammatory human epidermis, cell cultures and embryonal cells - Bayerl, Christiane; Brandt, H.; Niemczyk, M.; Müller-Decker, Karin; Gretz, Norbert (Inflammation research, 2003)
Objective: PAF-R (platelet activating factor-receptor) has been found on human keratinocytes to bind PAF, a proinflammatory phospholipid. We aimed to study PAF-R in a range of dermal cell lines and in samples of normal and psoriatic human skin to learn about its further role in humans.Methods: PAF-R was labeled immunocytochemically, histochemically and additionally studied with western blotting in human keratinocytes, human fibroblasts, embryonal keratinocytes, tumor cell lines and samples of normal and psoriatic human skin.Results: Keratinocytes from adult and embryonal epidermis of the 20th week of pregnancy showed a low level of labeling for PAF-R, but 3 ± 0.05% of plantar keratinocytes from adults were positive as were 4.2 ± 0.05% of embryonal plantar keratinocytes from the 21st week of pregnancy. In fibroblasts from adult and embryonal epidermis the protein was expressed at low levels. Western blotting revealed PAF-R positive bands at 67 k.Da in normal human skin and psoriasis, in psoriasis additionally at 45 k.Da. A 68 k.Da band was found in the colon cancer line HT 29 (control), and HaCaT cells, in embryonal keratinocytes additionally at 116 k.Da.Conclusions: PAF-R seems not to be important for embryonal or adult fibroblasts. In embryonal keratinocytes it is turned on after the 21st pregnancy week in a few cells seen as a band of 67 k.Da and at 116 k.Da, the latter is not found in adult keratinocytes. An additional 45 k.Da band of PAF-R was found in psoriasis that might stand for a truncated receptor. In the epithelial tumor cell line HaCaT and the HT29 colon cancer cell line PAF-R characterizes the anti-apoptotic effect of this receptor propagating tumor proliferation.